Crnkl1 is a highly selective regulator of intron-retaining HIV-1 and cellular mrnas - Xiao, Han; Wyler, Emanuel; Milek, Miha; Grewe, Bastian; Kirchner, Philipp; Ekici, Arif Bülent; Silva, Ana Beatriz Oliveira Villela; Jungnickl, Doris; Full, Florian; Thomas, Marco; Landthaler, Markus; Enßer, Armin; et al. (mBio, 2021)
The HIV-1 Rev protein is a nuclear export factor for unspliced and incom-pletely spliced HIV-1 RNAs. Without Rev, these intron-retaining RNAs are trapped in the nucleus. A genome-wide screen identified nine proteins of the spliceosome, which all enhanced expression from the HIV-1 unspliced RNA after CRISPR/Cas knockdown. Depletion of DHX38, WDR70, and four proteins of the Prp19-associated complex (ISY1, BUD31, XAB2, and CRNKL1) resulted in a more than 20-fold enhancement of unspliced HIV-1 RNA levels in the cytoplasm. Targeting of CRNKL1, DHX38, and BUD31 affected nuclear export efficiencies of the HIV-1 unspliced RNA to a much larger extent than splicing. Transcriptomic analyses further revealed that CRNKL1 also suppresses cyto-plasmic levels of a subset of cellular mRNAs, including some with selectively retained introns. Thus, CRNKL1-dependent nuclear retention is a novel cellular mechanism for the regulation of cytoplasmic levels of intron-retaining HIV-1 mRNAs, which HIV-1 may have harnessed to direct its complex splicing pattern. IMPORTANCE To regulate its complex splicing pattern, HIV-1 uses the adaptor protein Rev to shuttle unspliced or partially spliced mRNA from the nucleus to the cyto-plasm. In the absence of Rev, these RNAs are retained in the nucleus, but it is unclear why. Here we identify cellular proteins whose depletion enhances cytoplas-mic levels of the HIV-1 unspliced RNA. Depletion of one of them, CRNKL1, also increases cytoplasmic levels of a subset of intron-retaining cellular mRNA, suggesting that CRNKL1-dependent nuclear retention may be a basic cellular mechanism exploited by HIV-1.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Association; CRNKL1; Human immunodeficiency virus; Intron-retaining RNA; Nuclear retention; RNA splicing